Fintech credit, credit information sharing and bank stability: some international evidence - Nguyen Thanh Liem; Tran Hung Son; Ho Huu Tin; Nguyen Thi Canh (Cogent Business & Management, 2022)
This study relies on an aggregate dataset of 73 countries from 2013 to 2018 to investigate the nexus between fintech credit, credit information sharing on bank stability. We document several significant findings. First, our evidence implies that fintech credit tends to improve bank stability. This suggests that as fintech credit grows, it certainly competes with banks, but it also strengthens banks' stability. Second, credit information sharing increases bank stability. Thirdly, it is found that the impact of fintech credit on bank stability may depend on credit information sharing. Specifically, the presence of credit information sharing institutions may facilitate the positive effect of fintech credit on bank stability. This result remains unchanged to the introduction of alternative regression, as well as an alternative dependent variable. Finally, policy implications are discussed based on the findings of the research.
Keywords: F21; G32; Q55; 650; bank stability; credit information sharing; fintech